Consentimento do ofendido e estado democrático de direito: uma possível aplicação a casos de contribuição à autocolocação em risco e heterocolocação consentida em risco - Linhares, Antonio Carlos Alves (2018)
This research aims to contribute to finding solutions for problems orginates from consistent cases to practiced by a third-party in both in danger self-positioning and multi-positioning with consent of the victim. In order to do so, we evaluate the possibility that the solution to the former questions be oriented by the category of the consent of the victim, being this the tested hipothesys. This proposition consists of reconsidering the leading role of the victim when demonstrating his or her will to assume and take risks in hazardous activities, and its consequences in criminal law. Also, this study aims to propopse solutions which are more practical and applicable regarding jurisprudential incidence.